Bibliographic instruction and critical thinking - Ballesteros, Kathleen Lourdes M. (2004)
With the increasing bulk of information produced as well as with the increasing reliance on global network, there is a need to educate more information literate students. The current situation is providing an opportunity for librarians to play a major role in providing the student the needed skills in dealing with the fast changing environment of information and information technology. It is one of the responsibilities of librarians to educate independent information seekers.